Implementasi Program Tadabbur Al-Quran Dalam Meningkatkan Pemahaman Isi Kandungan Al-Quran Siswa Di SMP Muhammadiyah 1 Medan - Aulia, Adinda Putri; Nasution, Abdul Fattah; Pulungan, Juli Julaiha (Ikatan Da'i Indonesia, 2024)
The study entitled “Implementation of the Al-Quran Tadabbur Program in Improving Students’ Understanding of the Contents of the Al-Quran at SMP Muhammadiyah 1 Medan” aims to understand the implementation of the Al-Quran tadabbur program. This research method is qualitative descriptive, using data collection techniques with triangulation and data analysis. The results of the study indicate that the Al-Quran tadabbur program at SMP Muhammadiyah 1 Medan improves students’ understanding of the Al-Quran through guidance, discussion, and application of teachings in everyday life. The benefits of this program include improving understanding of the contents of the Al-Quran and making speeches. Supporting factors for the program include motivation, student readiness, focus, and teacher ability. Obstacles include lack of motivation, forgetting to bring the Al-Quran, short time, and lateness of participants. The implementation of the Al-Quran tadabbur program at SMP Muhammadiyah 1 Medan has been carried out well and provides benefits for students and teachers.